Long-run relationship between Islamic stocks returns and macroeconomic variables: An application of the autoregressive distributed lag model - Abd Majid, M. Shabri; Mohd Yusof, Rosylin (Emerald Group Publishing, 2009)
Purpose – The purpose of this paper is to explore the extent to which macroeconomic variables affect the Islamic stock market behavior in Malaysia in the post 1997 financial crisis period. Design/methodology/approach – The paper employs the latest estimation technique of autoregressive distributed lag (ARDL) model approach to cointegration. Findings – The results suggest that real effective exchange rate, money supply M3, treasury bill rate (TBR) and federal fund rate (FFR) seem to be suitable targets for the government to focus on, in order to stabilize the Islamic stock market and to encourage more capital flows into the market. As for the interest rates and stock returns relationship, the paper finds that when interest rates rise either domestically (TBR) or internationally (FFR), the Muslim investors will buy more Shari’ah compliant stocks; thereby escalating the Islamic stock prices. Research limitations/implications – The results of this study are limited to the post 1997 financial crisis period until the beginning of the year 2006 for a small open economy, Malaysia. Practical implications – The paper reveals that both changes in the local monetary policy variables and in the US monetary policy as measured by the changes in the FFR have a significant direct impact on the Islamic stock market behavior in Malaysia. Originality/value – The paper adopts the latest time series econometrics technique to test for cointegration, ARDL. And it is among the earliest attempts to investigate the long-run effects of the macroeconomic variables changes either domestically or internationally on the Islamic stock market.